Report on "Partisan effects of information campaigns in competitive authoritarian elections: evidence from Bangladesh" by Ahmed et al. (2024) - Gunther Bensch; Julian Rose; Florian Neubauer; Jörg Ankel-Peters; Abel Brodeur (Institute for Replication (I4R), 2025)
This report compiles our recent comment on Ahmed, Hodler, and Islam (2024, AHI-2024) and our response to the authors' reply to our comment. Our report is one element in a concerted forensic reproduction of studies based on data collected by GDRI, a Bangladesh-based survey company. We appreciate the authors' acknowledgment of discrepancies in AHI-2024. These are consequential admissions given the forensic nature of this report. We also clarify that these discrepancies are likely to drive AHI-2024's main results. Furthermore, our response shows that the authors' reply contains new contradictions. Overall, our investigation of the paper, the study's documentation, and its replication package raise serious concerns about the integrity of the data and the study design.
Keywords: 330